The Effect of Dutch Eggplant Juice (Solanum Betaceum Cav) on the Prevention of Anemia in Adolescents - Ferasinta Ferasinta; Endah Zulya Dinata (KHD Production, 2024)
Anemia is a condition where the concentration of red blood cells is below normal. Anemia can be caused by damage to blood cells due to heavy exercise which generally causes a loss of iron (Fe) so that hemoglobin (Hb) levels decrease. This study aims to determine the effect of Dutch eggplant juice in preventing anemia in adolescents. This research uses an experimental method, using a pre-experimental design with a pretest-posttest design. The instrument used in this research is an Hb measuring instrument, then the measurement results are observed. The results of the research show that there is an effect of giving tamarillo juice before and after with p-value = 0.000 (a<0.05). For further research, you can add comparative variables such as giving dragon fruit juice.